Potential of Chitosan-Encapsulated Mango Leaf Extract Nanoemulsion as Fruit Packaging - Putra, Panji Setya Utama; Adhika, Damar Rastri; Asri, Lia Amelia Tresna Wulan (Departemen Kimia, 2025)
Fruits have a relatively short shelf life. One of the extensively researched preservation methods for fruits is edible coating. Edible coating is a method of coating food products with a polymer layer. Considering the environmental and sustainability aspects, edible coatings were synthesized from biodegradable polymers derived from polysaccharides. Chitosan is a widely developed and researched type of biopolymer due to its antimicrobial activity. In addition to antimicrobial activity, antioxidant properties are important in food packaging applications. Mango leaves (Mangifera indica L.) contain various secondary metabolites that play a role in antioxidant activity, such as mangiferin, gallic acid, flavonoids, and gallotanin. In this study, mango leaf extract nanoemulsion was synthesized to improve the antioxidant and anti-UV properties of biopolymer chitosan-based fruit packaging. Mango leaf extract nanoemulsion was synthesized using surfactant and ultrasonication methods. The results of Particle Size Analyzer (PSA) measurements showed that the size of all nanoemulsions was 83-99 nm. Observations with Transmission Electron Microscope (TEM) showed that the nanoemulsion was spherical with a 15-46 nm size range. The UV-Vis spectrophotometer instrument was used to test antioxidant properties using the DPPH reagent and anti-UV activity. These tests showed that adding mango leaf extract concentration to the nanoemulsion system increased DPPH inhibition and absorbance against UV light. The results of the performance test of mango leaf extract nanoemulsion encapsulated by chitosan have a high potential to be used as a bio-based edible coating matrix and a substitute for materials that are difficult to degrade.